Islamic Banking Company Value Through Capital Adequacy, Problematic Financing and Efficiency - Amin, Asbi; Sulfati, Andi Sulfati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The purpose of this study is to examine the effect of capital adequacy, non-performing financing and efficiency on the value of companies in Islamic banking listed on the Indonesia Stock Exchange. registered with the Financial Services Authority (OJK). The population used in this study is Indonesian Sharia Commercial Banks (BUS) which are registered with the Financial Services Authority (OJK). The sampling technique in this study is non-probability sampling with purposive sampling technique. The analysis method used in this study is a quantitative data analysis method using the panel data regression method. The analysis was carried out by processing data through the Econometric Views (Eviews) program. The results of this study found that capital adequacy (CAR) had a positive and significant effect on the Company's value, while non-performing financing (NPF) could not have an effect on the Company's value and efficiency (OEOI) could not have an effect on the Company's value.